2008
DOI: 10.1111/j.1365-2583.2008.00779.x
|View full text |Cite
|
Sign up to set email alerts
|

A microarray‐based analysis of transcriptional compartmentalization in the alimentary canal of Anopheles gambiae (Diptera: Culicidae) larvae

Abstract: The alimentary canal of the larval mosquito displays a considerable degree of physiological compartmentalization among its different anatomical sub-divisions (gastric caeca, anterior midgut, posterior midgut and hindgut). We performed a comparative microarray analysis in order to identify transcripts which are particularly enriched in each gut section. Based on the available annotation of the selected transcripts, we suggest that the metabolism and absorption of proteins and carbohydrates takes place mainly in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 53 publications
2
41
0
Order By: Relevance
“…When VectorBase (www.vectorbase.org) expression maps are searched for Anopheles gambiae and Aedes aegypti NOX4-art genes (AGAP003772 and AAEL010179, respectively), we find differential expression during embryonic development [62, 63] and between tissues [64, 65] and increased expression after a blood meal [66, 67]. In Aedes aegypti , infection with Micrococcus luteus or Wolbachia (wMel strain) also increases NOX4-art expression [68, 69].…”
Section: Discussionmentioning
confidence: 99%
“…When VectorBase (www.vectorbase.org) expression maps are searched for Anopheles gambiae and Aedes aegypti NOX4-art genes (AGAP003772 and AAEL010179, respectively), we find differential expression during embryonic development [62, 63] and between tissues [64, 65] and increased expression after a blood meal [66, 67]. In Aedes aegypti , infection with Micrococcus luteus or Wolbachia (wMel strain) also increases NOX4-art expression [68, 69].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a microarray assay identified the expression of three Croquemort transcripts in the midguts of fourth-instar A. gambiae larvae. In this study, the Croquemort SCRBQ2 transcript was found to be enriched in the gastric caeca and in the hindgut/Malpighian tubules versus its expression in whole larvae (Neira Oviedo et al, 2008). Changes in Croquemort SCRBQ2 mRNA abundance have also been described in the midguts of female A. gambiae mosquitoes upon Plasmodium berghei ookinete invasion (Dong et al, 2006), but the role, if any, of this molecule during parasite infection remains unknown.…”
Section: Introductionmentioning
confidence: 77%
“…SCRBQ1 and SCRBQ4 expression was slightly up-regulated in late larval stages, while SCRBQ3 transcript was present mainly in third instar larvae and its expression in other developmental stages was more restricted, in contrast to the other Croquemort transcripts. Recently, data obtained from a microarray assay also identified the expression of Croquemort transcripts SCRBQ1, SCRBQ2, and SCRBQ3 in the midguts of fourth-instar A. gambiae larvae, however, Croquemort transcript SCRBQ4 was not detected in these assays (Neira Oviedo et al, 2008). We detected the presence of all four Croquemort transcripts in fourth-instar larvae, although we did not perform dissections of individual organs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…gambiae , mRNA transcripts of antimicrobial peptides Defensin 1 , Cecropins , Gambicin , as well as TEP1 , are enriched in the proventriculus [55]. TEP1 is also expressed in the neighboring gastric caeca during larval stages [57]. Future studies may clarify whether proventriculus-expressed TEP1 has a function that bypasses the requirement for LRM1 and APL1-C, perhaps in the lumen of the digestive tract where TEP1 could interact with the gut microbiota.…”
Section: Discussionmentioning
confidence: 99%